Anti-inflammatory, antinociceptive, and antipyretic effects of Lantana trifolia Linnaeus in experimental animals. - Uzcátegui, Bercy; ívilaDinorah; Suárez-Roca, Heberto; Quintero, Luis; Ortega, José; González, Beatriz (Investigación Clínica, 2009)
Lantana trifolia L. (Verbenaceae) is traditionally used as an anti-inflammatory medicinal plant in Venezuela. The methanol extract of the aerial parts of L. trifolia were assessed for the anti-inflammatory, anti-nociceptive and anti-pyretic properties. The extract produced an inhibition of carrageenan-induced edema in the rat paw over a dose range of 10-300 mg/kg i.p.; the dose-response curve was bell-shaped with a maximal effect at 100 mg/kg. The extract also produced a small but significant increase in the response latency of rats subjected to the hot plate, a thermal pain test that only detects analgesia by high-efficacy agents. The extract did not exhibit antipyretic activity. Thus, the L. trifolia extract could have therapeutically relevant anti-inflammatory and analgesic properties in humans.